Effects of homework creativity on academic achievement and creativity disposition: Evidence from comparisons with homework time and completion based on two independent Chinese samples - Fan, Huiyong; Ma, Yidan; Xu, Jianzhong; Chang, Ying; Guo, Shengli (Frontiers in Psychology, 2022)
During the past several decades, the previous studies have been focusing on the related theoretical issues and measuring tool of homework behaviors (mainly including homework time, completion and homework creativity). However, the effects of these homework behaviors on general creativity remain unknown. Employing a number of questionnaires, the present project investigated two samples from middle schools of mainland China. The results showed that: (1) the eight-item version of Homework Creativity Behaviors Scale had acceptable validity and reliability; (2) compared with homework completion and homework time, homework creativity explained less variety of academic achievement (3.7% for homework creativity; 5.4% for completion and time); (3) homework creativity explained more variance of general creativity than that of homework completion and homework time accounted (7.0% for homework creativity; 1.3% for completion and time); (4) homework creativity was negatively associated with grade level. Contrary to the popular beliefs, homework completion and homework creativity have positive effects on the students’ general creativity. Several issues need further studies were also discussed.